MENDIDIK KEMANDIRIAN USAHA MIKRO KECIL MENENGAH (UMKM) DENGAN WORKSHOP MARKETING DIGITAL DI DESA PRANGGRONG BOYOLALI - Khoir, Mulyanto Abdullah; Baidan, Nashruddin (AL HAZIQ: Journal of Community Service, 2025)
The workshop with the theme "Educating Independence of Micro, Small and Medium Enterprises (UMKM) Independence with Digital Marketing Workshop in Pranggrong Village Boyolali" aims to improve the understanding and skills of UMKM actors in utilizing digital technology as a marketing tool. This activity is motivated by the importance of digitalization in expanding market reach and increasing the competitiveness of local products in the modern era. This workshop includes material on the basic concepts of digital marketing, marketing strategies through social media and marketplaces, and the practice of creating attractive promotional content. Through interactive sessions and direct practice, participants are equipped with skills to utilize various digital platforms to market their products effectively. The results of this activity show that participants have a better understanding of digital marketing strategies and are able to apply them in their businesses. This workshop is expected to be the first step in encouraging UMKM actors in Pranggong Village to utilize digital technology optimally, so that they can expand the market and increase business growth.